Essays in Family Economics and Gender - Jacob, George (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Economics, 2023)
This dissertation consists of three essays on family economics and gender. It delves into the problems families face with an emphasis on women. The first essay looks at how parents with different preferences take joint decisions on parenting. I show how parents who have the same preferences on consumption but have differences in altruism and how they discount the future of the child, take strategic parenting decisions. I show how the more altruistic parent strategically allows the parenting decision to be aligned with the preferences of the less altruistic parent to gain her say in other household decisions. The second essay is focused on how family structures affect female labour force participation in the Indian context. I show that the death of a mother-in-law increases college educated daughter-in-law's participation in salaried jobs. In this essay, I also provide a plausible explanation of why female labour force participation and education are moving in different directions in India. In the third essay, I quantify how the risk of women experiencing intimate partner violence (IPV) for the first-time changes as they progress through different stages in life. I show that (in Europe) women are at the highest risk to experience IPV for the first time when they are young and potentially dating (age 22). I also evaluate how the existence of domestic violence laws and a national helpline for victims and survivors of IPV affect the risk of IPV at different stages in life.
APPROVED
Keywords: Parenting; Intimate Partner Violence; Female Labour Force Participation; Nash Bargaining; Social Norms; Decision Making; Power Dynamics; Marriage